2019
DOI: 10.5005/jp-journals-10031-1248
|View full text |Cite
|
Sign up to set email alerts
|

Self-perceived Oral Health, Satisfaction with Overall Health and Quality of Life Comparisons between Patients with Oral Lichen Planus and their Matched Controls

Abstract: Background: Oral lichen planus (OLP) is one of the most prevalent oral mucosal diseases. Aims: The aim of this study is to compare the quality of life, self-perceived oral health, satisfaction with health, and their potential predictors in OLP patients and their matched controls. Materials and methods: The study included 132 cases and 133 controls matched to cases by age, gender, and urbanization. The information about disease-related outcomes and predictors was acquired from a structured questionnaire and sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Complaints about food intake make healthy eating more difficult and also affect the patients’ social lives resulting in a reduced quality of life and psychological impairment. A study of the self-assessment of oral health, satisfaction with overall health and quality of life of patients with OLP compared to a healthy control group found that those affected suffered particularly from the negative effects of daily life and restrictions of eating [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Complaints about food intake make healthy eating more difficult and also affect the patients’ social lives resulting in a reduced quality of life and psychological impairment. A study of the self-assessment of oral health, satisfaction with overall health and quality of life of patients with OLP compared to a healthy control group found that those affected suffered particularly from the negative effects of daily life and restrictions of eating [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further longitudinal study to assess overtime change of OIDP intensity, taking into account previous or ongoing treatment, would be required for better understanding on the impacts of OLP treatment on patients’ quality of life. Second, some of the previous studies performed multivariate analysis where confounding factors were taken into account [ 28 , 35 ]. However, this study applied only univariate analyses due to a relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…In order to use these instruments, there is a need for cross-cultural adaption and validation of the methodology [ 26 ]. A number of previous studies have examined OHRQoL in OLP patients [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Most studies were conducted with the cross-sectional design.…”
Section: Introductionmentioning
confidence: 99%